The Sensitizing Effects of NOx on Methane Low-temperature Oxidation in a Jet Stirred Reactor - Marrodán Bretón, Lorena; Song, Yu; Vin, Nicolas; Herbinet, Olivier; Assaf, Emmanuel; Fittschen, Christa; Stagni, Alessandro; Faravelli, Tiziano; Alzueta, María Uxue; Battin-Leclerc, Frédérique (Jornada de Jóvenes Investigadores del I3A, 2018)
Biogas (mainly methane and carbon dioxide) produced from biomass anaerobic digestion is considered as a potential renewable gas-phase fuel. That is why the study of the mutual effects of CH4/NOx have attracted considerable attention in the past decade. In this work, the oxidation of methane with and without NOx addition has been investigated in a jet-stirred reactor.